Katy Duck meets the babysitter - Capucilli, Alyssa Satin, 1957- (Ready-to-read. Level one, Star reader!, 2012)
Katy Duck is unhappy about staying home when her parents go to a party, but her babysitter's bag full of scarves provides a lot of fun.